High-viscosity slurry as well as preparation method and application thereof

By mixing bentonite, carboxymethylcellulose and anhydrous sodium carbonate with water in a specific ratio, a high viscosity mud was prepared, which solved the problem of low mud viscosity and easy collapse of holes in non-excavation directional drilling technology, especially in alkaline water environments, which showed significant construction efficiency and safety improvement.

CN119775981APending Publication Date: 2025-04-08CHINA RAILWAY FIRST GRP ELECTRICAL SERVICE ENG CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202311286313.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-07
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

In the existing non-excavation directional drilling technology, the proportion and production methods of mud cannot effectively adapt to different geological environments, and the problem of low mud viscosity and easy collapse of holes in alkaline water environments has not been effectively solved.

Method used

A high viscosity mud is prepared by mixing bentonite, carboxymethylcellulose and anhydrous sodium carbonate with water, and is prepared by mixing slurry with high viscosity and stability. It is suitable for long-distance directional tube pulling technology in alkaline water environments.

Benefits of technology

It is achieved to improve the viscosity of the mud during non-excavation directional drilling, avoid hole collapse problems, and exhibit high viscosity and low filtration loss in alkaline water environment, significantly improving construction efficiency and safety.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of trenchless directional river drilling, and provides high-viscosity slurry and a preparation method and application thereof.The high-viscosity slurry is prepared from, by mass, 8%-14% of bentonite, 0.2%-0.5% of carboxymethylcellulose, 0.5%-2% of anhydrous sodium carbonate and 83.5%-91.3% of water; the preparation method comprises the following steps: mixing water and bentonite to obtain bentonite slurry; mixing the bentonite slurry with carboxymethyl cellulose to obtain a mixed solution; and mixing the mixed solution with anhydrous sodium carbonate to obtain the slurry. By setting specific raw materials and proportions, after the obtained high-viscosity slurry is applied to a long-distance directional pipe drawing technology in an alkaline water environment, the construction problems of low slurry viscosity, easy hole collapse and the like in a trenchless directional drilling process can be solved; the viscosity of the slurry provided by the invention can reach up to 80.44 Pa.s, and the filter loss is only 22.6 mL / 30 min.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of trenchless directional drilling through rivers, and in particular to high-viscosity mud and a preparation method and application thereof. Background Art

[0002] Trenchless directional drilling construction technology has the advantages of little disturbance to the surrounding soil, low engineering cost and high work efficiency, and is gradually being applied in the fields of water supply and drainage, power communication, gas transmission, etc. The mud ejected by the directional drill bit during the drilling process is an important component of this technology. The mud can ensure that the hole will not collapse, and at the same time carry the drill bit to suspend the drill cuttings and cool the drill bit, so it is called the "blood" of directional drilling.

[0003] At present, trenchless directional drilling technology has the following main problems: 1. Mud companies on the market keep the proportion and production of mud confidential. How to make suitable mud according to different geological environments is currently lacking in this technology; 2. When drilling holes and pulling pipes with trenchless directional drilling technology, using nearby river water to prepare mud can save construction costs. However, the current research on the mud characteristics and permeability film formation of trenchless directional drilling technology is limited to neutral water. The acidity and alkalinity of the water body are not considered at the construction site, and the impact of water penetration in the soil layer on the stability of the mud is ignored. Summary of the invention

[0004] The purpose of the present invention is to overcome the problems existing in the prior art and provide a high-viscosity mud and a preparation method and application thereof.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a high-viscosity mud, which is prepared from raw materials containing the following mass percentages:

[0007] Bentonite 8-14%, carboxymethyl cellulose 0.2-0.5%, anhydrous sodium carbonate 0.5-2%, water 83.5-91.3%.

[0008] Preferably, the bentonite is sodium-based bentonite, calcium-based bentonite or alkali-calcium-based bentonite.

[0009] Preferably, the density of the carboxymethyl cellulose is 0.5 to 0.7 g / cm 3 .

[0010] The present invention also provides a method for preparing high-viscosity mud, comprising the following steps:

[0011] (1) mixing water and bentonite to obtain bentonite slurry;

[0012] (2) mixing bentonite slurry and carboxymethyl cellulose to obtain a mixed solution;

[0013] (3) Mixing the mixed solution with anhydrous sodium carbonate to obtain the slurry.

[0014] Preferably, the stirring speed of the mixing in step (1) is 80-100 r / min, the mixing time is 10-20 min, and the mixing temperature is 20-30°C.

[0015] Preferably, the stirring speed of the mixing in step (2) is 80-100 r / min, the mixing time is 10-20 min, and the mixing temperature is 20-30°C.

[0016] Preferably, the stirring speed of the mixing in step (3) is 80-100 r / min, the mixing time is 10-20 min, and the mixing temperature is 20-30°C.

[0017] The invention also provides the application of high-viscosity mud in the long-distance directional pipe drawing technology in an alkaline environment.

[0018] The beneficial effects of the present invention are:

[0019] (1) The present invention provides a high-viscosity mud, comprising the following raw materials in percentage by mass: 8-14% bentonite, 0.2-0.5% carboxymethyl cellulose, 0.5-2% anhydrous sodium carbonate, and 83.5-91.3% water; the high-viscosity mud obtained by setting specific raw materials and proportions in the present application is applied to long-distance directional pipe pulling technology in an alkaline water environment, which can solve the construction problems of low mud viscosity and easy hole collapse in the process of trenchless directional drilling; the viscosity of the mud provided by the present invention can be as high as 80.44 Pa·s, and the filtration loss is only 22.6 mL / 30 min.

[0020] (2) The main component of the bentonite in the present invention is montmorillonite, which accounts for about 80% of the entire bentonite mineral. Montmorillonite is a silicate clay mineral. Due to its molecular structure and lattice substitution characteristics, bentonite with a high montmorillonite content is easy to disperse, has a large cation exchange capacity, good stability and a high pulping rate; carboxymethyl cellulose is relatively stable in nature, and its sodium salt is white granular with a density of about 0.6 g / cm 3It is odorless and tasteless, but it can absorb water and swell. After dissolving in water, it is hydrolyzed into a transparent and viscous colloidal solution, thus increasing the viscosity of the solution; anhydrous sodium carbonate has two main functions. One is that it can provide an alkaline environment for the mud slurry to improve the stability of the bentonite mud, and the other is that as a dispersant, it can increase the activity of the mud and help increase the viscosity of the mud; the hydrated sodium carbonate reacts chemically with the calcium, magnesium, silicon, aluminum and other components in the montmorillonite, destroying the lattice structure of the montmorillonite, and converting the amorphous silicon atoms in the montmorillonite crystal structure into active silicon atoms, achieving the purpose of activation, thereby improving the stability of the mud; the dispersion of sodium carbonate on the slurry in water promotes the The slurry, especially the solid particles, are both hydrated and decomposed, so that the solid particles are better suspended and dispersed in the entire slurry. Sodium carbonate can also be electrolyzed into a small amount of sodium ions and anions when dissolved in water. The sodium ions can be exchanged with the cations adsorbed on the surface of the bentonite solid particles, thereby increasing the concentration of exchangeable cations in the bentonite slurry. According to the double layer theory, after the sodium ions are hydrated, a thicker hydration film can be formed on the surface of the clay particles. In addition, the anions electrolyzed by sodium carbonate will react with the anions on the surface of the clay particles, causing the charged properties of the clay particle surface to change, which causes the card-structured clay particle polymer to be destroyed, thereby playing a role in dispersing the sticky particles of the mud. DETAILED DESCRIPTION

[0021] The present invention provides a high-viscosity mud, which is prepared from raw materials containing the following mass percentages:

[0022] Bentonite 8-14%, carboxymethyl cellulose 0.2-0.5%, anhydrous sodium carbonate 0.5-2%, water 83.5-91.3%.

[0023] In the present invention, the mass percentage of the bentonite is 8-14%, preferably 10-12%, and more preferably 11%.

[0024] In the present invention, the mass percentage of the carboxymethyl cellulose is 0.2-0.5%, preferably 0.25-0.45%, and more preferably 0.3-0.4%.

[0025] In the present invention, the mass percentage of the anhydrous sodium carbonate is 0.5-2%, preferably 0.8-1.6%, and more preferably 1-1.5%.

[0026] In the present invention, the mass percentage of water is 83.5-91.3%, preferably 83.9-90.9%, and more preferably 86-89%.

[0027] In the present invention, the bentonite is preferably sodium-based bentonite, calcium-based bentonite or alkali-calcium-based bentonite.

[0028] In the present invention, the density of the carboxymethyl cellulose is preferably 0.5 to 0.7 g / cm 3 , more preferably 0.55 to 0.65 g / cm 3 , more preferably 0.6 g / cm 3 .

[0029] In the present invention, the carboxymethyl cellulose is preferably sodium carboxymethyl cellulose.

[0030] The present invention also provides a method for preparing high-viscosity mud, comprising the following steps:

[0031] (1) mixing water and bentonite to obtain bentonite slurry;

[0032] (2) mixing bentonite slurry and carboxymethyl cellulose to obtain a mixed solution;

[0033] (3) Mixing the mixed solution with anhydrous sodium carbonate to obtain the slurry.

[0034] In the present invention, the stirring speed of the mixing in step (1) is preferably 80-100 r / min, more preferably 85-95 r / min, more preferably 90-93 r / min; the mixing time is preferably 10-20 min, more preferably 12-18 min, more preferably 13-15 min; the mixing temperature is preferably 20-30°C, more preferably 22-28°C, more preferably 25-26°C.

[0035] In the present invention, the stirring speed of the mixing in step (2) is preferably 80-100 r / min, more preferably 85-95 r / min, more preferably 90-93 r / min; the mixing time is preferably 10-20 min, more preferably 12-18 min, more preferably 13-15 min; the mixing temperature is preferably 20-30°C, more preferably 22-28°C, more preferably 25-26°C.

[0036] In the present invention, the stirring speed of the mixing in step (3) is preferably 80-100 r / min, more preferably 85-95 r / min, more preferably 90-93 r / min; the mixing time is preferably 10-20 min, more preferably 12-18 min, more preferably 13-15 min; the mixing temperature is preferably 20-30°C, more preferably 22-28°C, more preferably 25-26°C.

[0037] In the present invention, after the mixing is completed, the slurry is mixed completely without large agglomeration.

[0038] In the present invention, the pH value of the slurry obtained after the mixing in step (3) is preferably 7 to 9, more preferably 7.5 to 8.5, and even more preferably 8.

[0039] The invention also provides the application of high-viscosity mud in the long-distance directional pipe drawing technology in an alkaline environment.

[0040] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0041] Example 1

[0042] Sodium bentonite 8%, sodium carboxymethyl cellulose 0.2%, anhydrous sodium carbonate 0.5%, water 91.3%;

[0043] Prepare according to the following method:

[0044] Slowly add sodium bentonite into water and stir continuously at 90r / min at 25°C for 15min until there are no undissolved particles in the slurry to obtain bentonite slurry; weigh the density of 0.5g / cm 3 The sodium carboxymethyl cellulose was slowly added into the bentonite slurry, and the mixture was stirred at 90 r / min for 15 min at 25 °C to obtain a mixed solution; anhydrous sodium carbonate was weighed and slowly added into the mixed solution, and the mixture was stirred at 90 r / min for 15 min at 25 °C to obtain a mud, which was marked as A1.

[0045] The mass percentages of sodium carboxymethyl cellulose and anhydrous sodium carbonate were controlled to remain unchanged, and according to the preparation method of this embodiment, slurries with mass percentages of bentonite of 10%, 12%, and 14% were prepared respectively (the mass percentages of water were adjusted accordingly), and were marked as A2, A3, and A4, respectively.

[0046] The Yellow River Pipeline Project was selected as the background project. The geology was sandstone. The viscosity, specific gravity, filtration loss and pH of the A1-A4 muds prepared in this embodiment were measured and recorded. The results are shown in Table 1.

[0047] Table 1A1~A4 mud data

[0048] A1 A2 A3 A4 Mud viscosity / (Pa·s) 17.19 21.37 26.46 41.36 <![CDATA[Slurry specific gravity / (g / cm 3 )]]> 1.056 1.071 1.098 1.126 Filtration loss / (mL / 30min) 89.7 67.5 52.6 47.4 pH 8.31 8.17 8.52 8.65

[0049] According to Table 1, as the bentonite content increases, the effect of increasing the mud viscosity is general at first, and then it increases sharply. Analysis of the reasons shows that the main component of bentonite is montmorillonite. From a microscopic point of view, it is a silicate with a layered structure. It can absorb water equivalent to several times its own volume, dissolve in water to release negatively charged particles, and suspend and disperse well, so it can increase the viscosity of the slurry. When bentonite is added to water, it reacts quickly with water. When the bentonite content is large, the montmorillonite that contacts the aqueous solution first reacts first, and the montmorillonite that does not contact water reacts later. The montmorillonite that reacts first quickly forms a mud film, which prevents the solution from reacting with other montmorillonites, so it needs to be fully stirred and dissolved; the mud specific gravity also increases steadily. According to test data, for every 2% increase in bentonite content, the mud specific gravity also increases by 0.02g / cm 3 . When the bentonite content continues to increase, the trend of increasing mud density decreases. The reason may be that the bentonite content in the mud is too large and difficult to dissolve, forming insoluble substances at the bottom. Therefore, the obtained mud slurry is not uniform. At this time, when measuring the mud density, it should be left to stand for a period of time, and then the upper liquid should be taken for measurement; the filtration loss decreases, the bentonite content increases, the mud density and viscosity increase, and the molecules in the solution adsorb each other to form molecular clusters. Therefore, many particulate matter cannot pass through the sieve holes, resulting in a decrease in filtration loss; there is no obvious pattern in the change of pH value. According to the horizontal comparison of the data in Table 1, it is comprehensively obtained that the mud viscosity of A4 is larger and the filtration loss is smaller, which can be considered as a set of mud ratio data with better performance.

[0050] The mass percentage of sodium bentonite is controlled to be 14%, and the mass percentage of anhydrous sodium carbonate is controlled to be 0.5%. According to the preparation method of this embodiment, muds with mass percentages of sodium carboxymethyl cellulose of 0.2%, 0.3%, 0.4%, and 0.5% are prepared respectively (the mass percentage of water is adjusted accordingly), and are marked as B1, B2, B3, and B4 respectively.

[0051] The background project is the Yellow River Pipeline Project, the geology is sandstone, and the viscosity, specific gravity, filtration loss and pH of the B1-B4 muds prepared in this embodiment are measured and recorded. The results are shown in Table 2.

[0052] Table 2 Mud data of B1~B4

[0053] B1 B2 B3 B4 Mud viscosity / (Pa·s) 41.36 59.21 80.44 99.07 <![CDATA[Slurry specific gravity / (g / cm 3 )]]> 1.126 1.131 1.135 1.142 Filtration loss / (mL / 30min) 47.4 42.6 22.6 12.4 pH 8.65 8.71 8.49 8.55

[0054] According to the data in Table 2, it can be found that when the content of sodium carboxymethyl cellulose increases, the viscosity of the mud increases significantly. The reason for this is that the effect of sodium carboxymethyl cellulose content on the viscosity of the mud is related to the amount of solid particles in the mud. The solid particles of the mud are unevenly distributed in the slurry, and the particle molecules are connected to each other to form a spatial network flocculation structure. When the content of sodium carboxymethyl cellulose increases, the spatial network flocculation structure increases, so the viscosity increases; the mud specific gravity is less affected by sodium carboxymethyl cellulose. When the sodium carboxymethyl cellulose increases from 0.2% to 0.5%, the mud specific gravity increases from 1.126g / cm 3 Increased to 1.142 g / cm 3 ; The filtration loss of the mud changes significantly, because sodium carboxymethyl cellulose as a thickener can quickly increase the viscosity of the mud, so that the solid particles in the mud are suspended in the slurry of the mud, which reduces the filtration loss of the mud; the pH value remains stable, and when the content of sodium carboxymethyl cellulose increases, the pH is 7.49-7.71, with a change range of 2%. Therefore, the CMC content has little effect on the pH value of the mud. According to the horizontal comparison in Table 2, the muds of groups B3 and B4 have higher viscosity and lower filtration loss, but larger pieces of insoluble matter appear in the mud of group B4, so B3 is a group of mud ratio data with better performance.

[0055] The mass percentage of sodium bentonite and the mass percentage of sodium carboxymethyl cellulose were controlled to be 14% and 0.4%, and muds with mass percentages of anhydrous sodium carbonate of 0.5%, 1%, 1.5% and 2% were prepared respectively according to the preparation method of this embodiment (the mass percentage of water was adjusted accordingly), and were marked as C1, C2, C3 and C4 respectively.

[0056] The Yellow River Pipeline Project was selected as the background project. The geology was sandstone. The viscosity, specific gravity, filtration loss and pH of the C1-C4 muds prepared in this embodiment were measured and recorded. The results are shown in Table 3.

[0057] Table 3 C1~C4 mud data

[0058] C1 C2 C3 C4 Mud viscosity / (Pa·s) 80.44 57.58 45.22 39.35 <![CDATA[Slurry specific gravity / (g / cm 3 )]]> 1.135 1.247 1.256 1.262 Filtration loss / (mL / 30min) 22.6 24.7 28.9 29.6 pH 8.49 8.85 8.26 9.64

[0059] According to the data in Table 3, it can be found that as the sodium carbonate content increases, the viscosity decreases sharply, from 80.44 to 39.35. Therefore, sodium carbonate can effectively reduce the viscosity of mud. The reason is that the ion groups obtained by the ionization of sodium carbonate in water react with the montmorillonite colloidal particles of bentonite, which reduces the viscosity of mud. When the sodium carbonate content increases, the cation concentration also increases, which increases the pH value of the mud and promotes the ionization reaction in the slurry, so the viscosity decreases; the increase in mud specific gravity is small, and the mud specific gravity is 1.135-1.262 g / cm 3, the specific gravity of the slurry changes within 2%, indicating that the increase in the content of sodium carbonate from 0.5% to 2% has little effect on the specific gravity of the mud. The reason for this is that the dispersing effect of sodium carbonate on the slurry in water promotes the hydration and decomposition of solid particulate matter in the mud slurry, making the solid particles easy to disperse in the entire slurry; the mud filtration loss remains basically unchanged. The reason for this is that the montmorillonite particles in the bentonite are negatively charged, and the positively charged sodium ions ionized by sodium carbonate dissolved in water increase with the increase of the sodium carbonate content. Sodium ions are strong ions, and a large number of sodium ions enter the bound counterion layer due to mutual repulsion. The double electrical layer is compressed, the charge repulsion decreases, and the filtration loss increases; the pH value increases linearly, because sodium carbonate dissolves in water and ionizes carbonate ions, and the carbonate ions undergo hydrolysis to form carbonic acid and hydroxide ions, so the solution is alkaline, and with the increase of sodium carbonate content, the concentration of hydroxide ions also increases, and the pH value of the mud also increases. According to the horizontal comparison in Table 3, it can be concluded that the mud viscosity of C1 is larger and the filtration loss is smaller, which can be considered as a set of mud ratio data with better performance.

[0060] Through the above orthogonal test, it can be concluded that bentonite: sodium carboxymethyl cellulose: sodium carbonate: water = 140:4:5:851 is a good mud ratio.

[0061] Example 2

[0062] Calcium bentonite 14%, sodium carboxymethyl cellulose 0.3%, anhydrous sodium carbonate 0.5%, water 85.2%;

[0063] Prepare according to the following method:

[0064] Calcium-based bentonite was slowly added into water and stirred continuously at 95 r / min at 28°C for 13 min until there were no more undissolved particles in the slurry to obtain bentonite slurry; the density was weighed to be 0.6 g / cm 3 The sodium carboxymethyl cellulose was slowly added into the bentonite slurry, and the mixture was stirred at 95 r / min for 13 min at 28 °C to obtain a mixed solution. Sodium carbonate was weighed and slowly added into the mixed solution, and the mixture was stirred at 95 r / min for 13 min at 28 °C to obtain a mud.

[0065] The same detection method as in Example 1 was adopted to obtain the viscosity of the mud prepared in this example to be 76.56 Pa·s and the specific gravity to be 1.072 g / cm 3 The filtration loss was 27.9 mL / 30 min and the pH value was 8.20.

[0066] Example 3

[0067] Calcium alkali bentonite 9%, sodium carboxymethyl cellulose 0.4%, anhydrous sodium carbonate 1%, water 89.6%;

[0068] Prepare according to the following method:

[0069] Slowly add alkali calcium bentonite into water and stir continuously at 85r / min at 22°C for 18min until there are no undissolved particles in the slurry to obtain bentonite slurry; weigh the density of 0.7g / cm 3 The sodium carboxymethyl cellulose was slowly added into the bentonite slurry, and the mixture was stirred at 85 r / min for 18 min at 22 °C to obtain a mixed solution. Sodium carbonate was weighed and slowly added into the mixed solution, and the mixture was stirred at 85 r / min for 18 min at 22 °C to obtain a mud.

[0070] The same detection method as in Example 1 was adopted to obtain the viscosity of the mud prepared in this example to be 71.79 Pa·s and the specific gravity to be 1.121 g / cm 3 The filtration loss was 28.2 mL / 30 min and the pH value was 8.76.

[0071] It can be seen from the above embodiments that the present invention provides a high-viscosity mud, which, after being applied to the long-distance directional pipe pulling technology in an alkaline water environment, can solve the construction problems such as low mud viscosity and easy hole collapse in the process of non-excavation directional drilling; the mud viscosity provided by the present invention can be as high as 80.44Pa·s, and the filtration loss is as low as 22.6mL / 30min.

[0072] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A high viscosity mud, characterized in that: Prepared from raw materials containing the following mass percentages: Bentonite 8-14%, carboxymethyl cellulose 0.2-0.5%, anhydrous sodium carbonate 0.5-2%, water 83.5-91.3%.

2. The high viscosity mud according to claim 1, characterized in that: The bentonite is sodium-based bentonite, calcium-based bentonite or alkali-calcium-based bentonite.

3. The high viscosity mud according to claim 1 or 2, characterized in that: The density of the carboxymethyl cellulose is 0.5-0.7 g / cm 3 .

4. The method for preparing high viscosity mud according to any one of claims 1 to 3, characterized in that: It includes the following steps: (1) mixing water and bentonite to obtain bentonite slurry; (2) mixing bentonite slurry and carboxymethyl cellulose to obtain a mixed solution; (3) Mixing the mixed solution with anhydrous sodium carbonate to obtain the slurry.

5. The preparation method according to claim 4, characterized in that: The stirring speed of the mixing in step (1) is 80-100 r / min, the mixing time is 10-20 min, and the mixing temperature is 20-30° C.

6. The preparation method according to claim 5, characterized in that: The stirring speed of the mixing in step (2) is 80-100 r / min, the mixing time is 10-20 min, and the mixing temperature is 20-30° C.

7. The preparation method according to claim 6, characterized in that: The stirring speed of the mixing in step (3) is 80-100 r / min, the mixing time is 10-20 min, and the mixing temperature is 20-30° C.

8. Application of the high viscosity mud according to any one of claims 1 to 3 in long distance directional pipe drawing technology in an alkaline environment.

Citation Information

Cited By

  • Slurry containing bentonite and preparation method and application thereof

    CN120682778A